Extraction of Spatial Ultrasonic Wave Packet Features by Exploiting a Modified Hough Transform - Ploß, Peter; Rupitsch, Stefan; Lerch, Reinhard (IEEE Sensors Journal, 2014)
This contribution presents a method for extracting spatial acoustic wave packet features from ultrasonic sound fields by exploiting a modified Hough transform. In ultrasound-based flow measurement systems, the fluid angle is defined as the angle under which the acoustic waves propagate with respect to the flow direction of the streaming fluid. This angle is a feature of the ultrasonic wave and is crucial for the exact calculation of the volume flow. With the proposed method, the angle can be determined reliably with an accuracy better 0: 1 from a spatially discretized sound pressure distribution that was measured or simulated. Furthermore, it allows for identifying the wave packet's wavelengths between neighboring wavefronts. The method is independent of the transducer design (i.e., angle beam or normal incidence). It is first verified and then applied to both simulated and measured data.
Keywords: Feature extraction; Hough transform; image processing; ultrasonic flow measurement; wavefront orientation